Pilot Study on Obstetric Brachial Plexus Paralysis: Docs Arm Swing Asymmetry Affect Foot Plantar Pressure Behavior? - Kuchimov, Shavkat Nadir; AKALAN, NAZİF EKİN (My University, 2019)
Introduction Brachial plexus palsy, as one of the most common congenital injuries affected by arm swing, is characterized by muscle weakness at different levels in the upper extremity (1). As the weakness of the upper extremity muscles can affect the trunk muscles and the postural development, these children may have some gait deviations (2,3). Previous studies have shown that walking parameters are also influenced by clinical conditions such as stroke and cerebral palsy (2-6). There is a lack of literature on determining the biomechanical influences of arm swing asymmetry on foot pressure behavior for OBBP children. Therefore, the aim of the study was determining arm-swing asymmetry related foot pressure behavioral alterations on OBBP. Research Question Does arm swing asymmetry affect foot plantar pressure behavior on OBBP patients? Methods Thirteen children with OBPP (7 females, 6 males) (mean age:9.37±2.68 years) participated in the study. For all individuals, a digital plantar-pressure analysis system (Win-track, Balma, France) was utilized to analyze the foot pressure behavior during standing and walking with self-selected velocity. The magnitude of the first and the second peak forces divided to an invidual’s weight (Fl, F2), total stance duration (Ts), time of Fl (Tl), time of min force between F1-F2 (T2), time o f F2 (T3), step length were calculated. Each stance phase was divided into five sub-phases: Loading response (Tl/Ts), mid-stance (T2-Tl/Ts), terminal stance (T3-T2/Ts) and pre-swing (Ts-T3/Ts), single limb support (T3-Tl/Ts) (7). In addition, arm swing ranges were recorded and analyzed using Kinovea software (8). Paired t-test was used for the compared between affected side and non-affected side (p < 0.05). Results Fl, pre-swing duration and step length were higher in affected side than in non-affected side(p<0.05). Single limb support duration lower in affected side than in non-affected side (p<0.05). The maximum arm flexion and extension angle and arm swing range were significantly reduced on the affected side (p<0.05). No significant difference was found in F2, loading response duration, mid-stance duration and terminal stance duration between affected side and non-affected side (Table 1). Discussion The reduced arm swing may alter the foot pressure behavior during walking on affected side as well as the non-affected side in children with OBBP. Reduced single limb support duration ((T3-Tl)/Ts) on the affected side indicate the stability problem in stance on affected side. Increase the first vertical peak force (Fl) on the affected side is probably related to the decreased arm extension range at the affected side, which absorbs the first peak of vertical force in early stance during walking. Increased step length on the affected side may due to the enhanced single limb duration on the non-affected side.